Beyond Romantic Ecocriticism - Nichols, A. author. aut Link
XXIII, 230 p. 6 illus.
Keywords: Nichols chronicles the Enlightenment view of 'Nature' as static and separate from humans as it moved towards the Romantic 'nature' characterized by dynamic links among all living things. Engaging Romantic and Victorian thinkers, as well as contemporary scholarship, he draws new conclusions about 21st-century ideas of nature.